Higher Education Policy on Student Engagement: Thinking Outside the Box. Issue 1 (March 2017) - Kahn, Peter
Abstract It has been suggested that higher education policy across the world is currently framed by a common set of assumptions. As a result, policy makers have a restricted sense of the options that are open to them. This paper looks to the paradigm of critical realism in order to open up alternative perspectives for policy makers. The argument specifically focuses on policy around student engagement, building on earlier theorising in this area. Student engagement is seen to be constituted by the agency of learners within educational settings, supported as this is by the social relations maintained by learners. The argument opens up alternative framings for policy in ways that take account of the reflexivity and relational goods that sustain the engagement of students in their studies, addressing areas such as teaching and learning, extra-curricular activity, human resources, the character of institutions and student protest.